2009
DOI: 10.1037/a0013381
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the relationship between moral judgment development and individual characteristics: The role of educational contexts.

Abstract: This study examines variation in moral judgment level as measured by the Defining Issues Test 2 (DIT-2; J. R. Rest & D. Narvaez, 1998), based on individual demographic information and educational contexts. Individual DIT-2 scores and demographic information were obtained from the archived data sets housed at the Center for the Study of Ethical Development. The information on educational contexts was obtained by surveying the researchers who initially gathered the data. Hierarchical linear modeling was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 33 publications
3
52
0
1
Order By: Relevance
“…The interactivity attributes of the modules, including in-class and online discussions among peers, was a significant contributor to increasing ethical reasoning in participants, although the effects were mixed (both positive and negative contributors). Research has suggested that moral judgment can be influenced by exposure to rich social contexts 20 as well as curricular interventions 42 , and may develop best when individuals have the opportunity to engage in discourse (including argumentation) about moral dilemmas 39 . Similarly, Hartwell 29 has indicated that student-centered moral discourse is one of the most successful curricular strategies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The interactivity attributes of the modules, including in-class and online discussions among peers, was a significant contributor to increasing ethical reasoning in participants, although the effects were mixed (both positive and negative contributors). Research has suggested that moral judgment can be influenced by exposure to rich social contexts 20 as well as curricular interventions 42 , and may develop best when individuals have the opportunity to engage in discourse (including argumentation) about moral dilemmas 39 . Similarly, Hartwell 29 has indicated that student-centered moral discourse is one of the most successful curricular strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The DIT-2 instrument presents five ethical scenarios, each of which are followed by 12 statements of reasoning related to the ethical dilemma presented. Respondents are asked to rank these 12 statements in terms of their importance, and then select the four most important to making a decision 42 . The EERI instrument was developed to assess ethical reasoning in an engineering context 60,64 , and is structured similar to the DIT-2, but the scenarios are specific to engineering contexts.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations